An Exploration of Curriculum Adequacy for Pre-Service Teachers of Learners With Special Needs - Udeme Samuel Jacob; Jace Pillay; Jeffrey Ifeanyichukwu Chisunum (Studies in Learning and Teaching, 2024)
This qualitative research utilised a phenomenological research design to explore the adequacy of the curriculum for pre-service teachers in preparing them to teach learners with special needs. The research involved purposive sampling of eight participants enrolled in a Professional Diploma in Education (PDE) program at a government-funded university in South-South, Nigeria. Data was collected through semi-structured interviews and thematically analysed using ATLAS.ti qualitative software. The research established trustworthiness through rigorous methodological approaches and ethical considerations. The research results indicated that the curriculum was suitable for pre-service teachers but unsuitable for students with special needs. It was discovered that the curriculum failed to adequately accommodate students with special needs, necessitating the need for changes to curriculum content, instructional materials, and delivery methods. Additionally, the research emphasised the lack of specific instructional programs designed to equip educators with the necessary skills and knowledge to effectively teach students with disabilities, suggesting a potential deficiency in teacher training. The findings of this research offer valuable insights that can inform the development and reform of curricula. These insights highlight the importance of consistently modifying and adapting curricula to address the changing educational demands, with a particular focus on special needs education.